Faktor-Faktor Penyebab Rendahnya Dukungan Keuangan Jemaat terhadap Pelaksanaan Pemberitaan Kabar Baik di GSKI Pokok Anggur Bekasi - Suhartono Suhartono; Rinto Francius Sirait; Deny Fery Supit (Pusat Riset dan Inovasi Nasional, 2026)
Many churches face significant challenges in effectively carrying out their Gospel mission amidst limited resources, and one such church is the GSKI Pokok Anggur Church in Bekasi. This research employed a qualitative method with a case study approach. Sampling was conducted using purposive sampling. The data collection techniques employed in this study included literature review, observation, the author's own experiences, and face-to-face interviews with texts, without direct involvement with eyewitnesses of events or other objects. The results of this study are as follows: First, the implementation of the missionary movement or evangelism at the GSKI Pokok Anggur Church in Bekasi exhibits profound problems, both conceptually and practically. Although the church has established a structural commitment through the formation of a mission group and established a work program, evangelism activities have not yet met expectations. Second, the congregation's low financial support for the missionary movement at the GSKI Pokok Anggur Church in Bekasi is a complex phenomenon, arising from the interaction of various theological, structural, and cultural-economic factors.